Minimal information: an urgent need to assess the functional reliability of recombinant proteins used in biological experiments - de Marco, Ario (BioMed Central, 2008)
Structural characterization of proteins used in biological experiments is largely neglected. In most publications, the information available is totally insufficient to judge the functionality of the proteins used and, therefore, the significance of identified protein-protein interactions (was the interaction specific or due to unspecific binding of misfolded protein regions?) or reliability of kinetic and thermodynamic data (how much protein was in its native form?). As a consequence, the results of single experiments might not only become questionable, but the whole reliability of systems biology, built on these fundaments, would be weakened. The introduction of Minimal Information concerning purified proteins to add as metadata to the main body of a manuscript would render straightforward the assessment of their functional and structural qualities and, consequently, of results obtained using these proteins. Furthermore, accepted standards for protein annotation would simplify data comparison and exchange. This article has been envisaged as a proposal for aggregating scientists who share the opinion that the scientific community needs a platform for Minimum Information for Protein Functionality Evaluation (MIPFE).